CRITICAL REVIEW ON SUPPORTIVE TREATMENT MEASURES IN ACUTE ALUMINUM PHOSPHIDE TOXICITY - Dr Santoshi Shrikant Mane; Dr Nilima Wadnerwar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Acute aluminum phosphide (AlP) poisoning represents one of the most challenging toxicological emergencies globally due to its high fatality rates and lack of a specific antidote. Phosphine gas, released upon AlP’s exposure to moisture or gastric acid, disrupts mitochondrial oxidative phosphorylation, generating reactive oxygen species and precipitating systemic multi-organ failure. The primary management approach is supportive care, encompassing aggressive hemodynamic stabilization, respiratory support, and correction of severe metabolic acidosis. However, the rapid progression of toxicity, coupled with resource limitations in many affected regions, often leads to poor outcomes. Emerging interventions, including antioxidant therapies, mitochondrial protective agents, and advanced extracorporeal techniques such as extracorporeal membrane oxygenation (ECMO), show potential for improving survival. Concurrently, research into biomarkers for early severity prediction and the development of phosphine-neutralizing agents offers hope for more targeted approaches. Addressing the high mortality associated with AlP poisoning requires a multidisciplinary strategy, combining advancements in clinical care, stricter regulation of AlP distribution, and public health initiatives to mitigate its misuse, particularly for self-harm. Future innovations and equitable access to advanced medical interventions are essential to reducing the global burden of this highly lethal poisoning.